Legal And Psychological Implications Of Divorce Refusal: A Case Study Of Decision No. 880/Pdt.G/2023/Pa. Tmg Based On Sema No. 1 Of 2022 - Sarkanto; Adewumi, Ibrahim Adeyemi; Price, Benjamin (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
This study analyses divorce denial's legal and psychological implications in case No. 880/Pdt.G/2023/PA.Tmg, based on the Supreme Court Circular (SEMA) No. 1 of 2022. The denial was due to the unmet requirement of a six-month separation period, despite evidence of continuous conflict and the husband's criminal behavior. The research examines whether the court considered the psychological aspects of both parties and how SEMA No. 1 of 2022 was applied. Methods This research uses a qualitative approach with case studies that analyze legal documents and court decisions related to the application of SEMA No. 1 of 2022 in divorce rejection cases; the findings highlight the need for legal flexibility to accommodate emotional and cultural factors in divorce cases, suggesting possible policy revisions to support affected individuals better.